Reconstructing Suffixal Phrasemes In Bantu Verbal Derivation - Bostoen, Koen; Guérois, Rozenn (My University, 2022)
This chapter introduces the notion of suffixal phrasemes to designate the semantically non-compositional complexes of suffixes which emerged across time and space in Bantu to renew morphology in several verbal derivation categories. It is shown that such verb derivational phrasemes can be reconstructed to different ancestral stages as far back as Proto-Bantu (PB) and possibly beyond. The oldest instance of such a suffixal phraseme in Bantu is the causative *-ɪdi, which is reconstructed to PB as the phraseologisation of applicative *-ɪd and the short causative *-i, in addition to the previously reconstructed simplex PB causative suffixes *-i and *-ic. The Bantu ancestral language that emerged after the North-Western Bantu branches had split off created a new causative marker, i.e. *-ɪki, through the non-compositional reanalysis of neuter *-ɪk and short causative *-i. Around the same stage, the long passive suffix *-ɪbʊ rose as an aggregation of the middle suffix *-Vb, well-attested in North-Western Bantu, and the short PB passive suffix *-ʊ. Much younger but still of considerable time-depth are reciprocal phrasemes produced out of a complex of PB associative/reciprocal *-an preceded by either causative *-ɪdi (i.e. *-ɪzyan) or intensive *-ang/*-ag/*-ak (most often *-angan). These causative, passive and reciprocal suffixes are all built on a final element that goes back to at least PB and whose semantics and syntax it copied. Other suffixal phrasemes rather adopted the role of their initial element, while stills others developed idiosyncratic functions in which the input of their historical components can only be inferred.
Keywords: suffixal phrasemes; Bantu; Verbal derivation